Feasibility and reliability of a newly developed antenatal risk score card in routine care. Issue 1 (January 2015) - van Veen, Mieke J.; Birnie, Erwin; Poeran, Jashvant; Torij, Hanneke W.; Steegers, Eric A.P.; Bonsel, Gouke J.
Abstract: Objective: to study in routine care the feasibility and inter-rater reliability of the Rotterdam Reproductive Risk Reduction risk score card (R4U), a new semi-quantitative score card for use during the antenatal booking visit. The R4U covers clinical and non-clinical psychosocial factors and identifies overall high risk pregnancies, qualifying for intensified antenatal care. Design: a population-based cross-sectional study (feasibility) and a cohort study (inter-rater reliability). Setting: feasibility was studied in six midwifery practices and two hospitals; the reliability study was performed in one midwifery practice. Participants: 1096 pregnant women in the feasibility study and a subsample of 133 participants in the inter-rater reliability study. Measurements: feasibility was expressed as (a) time needed to complete the R4U and (b) the missing rate at the item and client level. For inter-rater reliability (IRR) an independent, blinded, caregiver completed a re-test R4U during a second visit; inter-rater agreement for each item and all domain sum scores were computed. Findings: completion of the R4U took 5 minutes or less in 63%; and between 5 and 10 minutes in another 33%. On the participant level 0.2% of women had >20% missing values (below 4% threshold, P <0.001). One of 77 items had a >10% missing rate. The per item IRR was 100% in 20% of the items, and below the predefined 80% threshold in 13% of the items ( n =9). The domain sum scores universally differed less than the predetermined ±15% margin. Key conclusion: the R4U risk score card is a feasible and reliable instrument. Implication for practice: the R4U is suitable for the assessment of clinical and non-clinical risks during the antenatal booking visit in a heterogeneous urban setting in routine practice. Highlights: The poor Dutch perinatal outcomes suggest that improved risk assessment is needed. R4U antenatal card addresses clinical and non-clinical risks during history taking. R4U shows excellent feasibility and good inter-rater reliability. The risk accumulation does not support a simple high-/low-risk dichotomy. R4U is a suitable instrument to screen all risks in all pregnant women.